Gene Therapy of Periodontal Disease by AAV-shRNA Silencing of Cathepsin K by inhibiting inflammation in periodontal lesion area - Chen, Wei (J Periodontal Res, 2016)
BACKGROUND AND OBJECTIVE: Periodontitis is a serious disease that affects the majority of adult population around the world. While great efforts have been devoted toward understanding the pathogenesis of periodontitis, there remains a pressing need for developing potent therapeutic strategies for targeting this dreadful disease. In this study, we utilized adeno-associated virus (AAV) expressing Cathepsin K (Ctsk) shRNA (AAV-sh-Ctsk) to silence Ctsk in vivo and subsequently evaluated its impact in periodontitis as a potential therapeutic strategy for this disease. MATERIAL AND METHODS: We used a known mouse model of periodontitis, in which wild-type BALB/cJ mice were infected with Porphyromonas gingivalis W50 (P. gingivalis) in the maxillary and mandibular periodontium to induce the disease. AAV-sh-Ctsk was then administrated locally into the periodontal tissues in vivo, followed by analyses to assess the progression of the disease. RESULTS: AAV-mediated Ctsk silencing drastically protected mice (>80%) from P. gingivalis-induced bone resorption by osteoclasts. Also, AAV-sh-Ctsk administration drastically reduced inflammation by impacting the expression of many inflammatory cytokines as well as T cell and dendritic cell numbers in periodontal lesions. CONCLUSION: AAV-mediated Ctsk silencing can simultaneously target both the inflammation and bone resorption associated with periodontitis through its inhibitory effect on immune cells and osteoclast function. Thereby, AAV-sh-Ctsk administration can efficiently protect against periodontal tissue damage and alveolar bone loss, establishing this AAV-mediated local silencing of Ctsk as an important therapeutic strategy for potently treating periodontal disease.